Transaksi Jual Beli Dengan Sistem Member Card Dalam Perspektif Ekonomi Islam (Penelitian Pada Toko Sophie Paris Hibrida Bengkulu) - Istikomah Istikomah; Dira Rahmayeti (Institut Agama Islam Negeri Bengkulu, 2019)
The purpose of this study was to determine the legal system of member cards in buying and selling transactions in Sophie Paris Hybrid city of Bengkulu in the perspective of Islamic economics. This study used descriptive qualitative method. Data collection techniques carried out by observation, interviews and documentation. The research informants were determined by purposive sampling, namely the Business Center owner, Business Center assistant and member card user members. Data analysis was performed using data reduction techniques, data presentation and conclusion drawing. The results of this study conclude that: The member card system in buying and selling transactions at Sophie Paris who want to join as a member member pays Rp.70,000 registration fee, gets a bag, guidebook, and ID card, 30% discount on Sophie Paris catalog 20% Sunday catalog, bonuses and rewards for each rank up. The member card system in buying and selling transactions in the perspective of Islamic economics that is given free or paid at the beginning of registration is legitimate and permissible, if not contrary to Islamic economic principles. From the explanation of the fatwa institutions it can be understood that the member card system is not allowed to collect money for take advantage of consumers who want to become members, but the collection of money is permitted if the money withdrawn from the member card holder is only limited to the cost of making the card and the issuer does not take advantage of the card issuance at all. The member card system at Sophie Paris Hybrid with a paid system at the beginning of the registration must not be because the registration or administration money is not a substitute for making member card financing but registration money if you want to join as a member member.